Calibrating the leaf color chart for nitrogen management in different genotypes of rice and wheat in a systems perspective - Shukla, Arvind K.; Ladha, Jagdish K.; Singh, V.K.; Dwivedi, B.S.; Balasubramanian, Vethaiya; Gupta, Raj K.; Sharma, S.K.; Singh, Yogendra; Pathak, H.; Pandey, P.S.; Padre, Agnes T.; Yadav, R.L. (Wiley, 2004)
Low N use efficiency (NUE) continues to be a problem in the rice (Oryza sativa L.)–wheat (Triticum aestivum L.) cropping system. The leaf color chart (LCC)–based real‐time N management can be used to optimize/synchronize N application with crop demand or to improve existing fixed split N recommendations. We conducted a field experiment during 2001–2003 at Modipuram, India, to determine the threshold LCC values for N application in rice and wheat, assess the need for basal N application, calibrate the LCC with a chlorophyll meter (SPAD), and work out the economics of rice–wheat systems. Treatments consisted of LCC scores of 2 to 5 for different cultivars of rice and wheat and were compared with the zero‐N control and a recommended fixed‐time N splitting. In rice, LCC ≤ 3 for ‘Basmati‐370’, 4 for ‘Saket‐4’, and 5 for ‘Hybrid 6111/PHB‐71’ produced higher yield and NUE than recommended N splits. In wheat, maintenance of LCC ≤ 4 required 120 kg N ha−1, which produced higher grain yield, N uptake, and NUE than that of recommended N splits. Chlorophyll meter reading and crop growth rate (g m−2 day−1) at 15 d after transplanting in rice and 21 d after seeding in wheat were not significantly different with or without basal N application, indicating that basal N application in rice and wheat was not necessary in soils having relatively high indigenous N supply. Both LCC and SPAD readings (r = 0.84 to 0.91) were highly correlated in rice and wheat. Net returns were 19 to 31% higher in LCC‐based N management than in fixed‐time N application for rice–wheat cropping.